Public Private Partnership in Tourism Development during a Pandemic - Ach.Apriyanto Romadhan; Duwi Pratama; Asep Nurjaman (Jurnal Partisipatoris, 2022)
Public private partnership exists as a form of government innovation to improve the quality of public services. This is why every government agency continues to be required to continue to innovate. In the context of tourism development during the Malang city pandemic. TIC (Tourist Information Center) is an application that is being developed by the Malang City Government which is prepared to promote the tourism sector in Malang City, which is then carried out in collaboration between Gojek and Malang City Government. Malang City Government uses a public private partnership model of cooperation. The method used in this research is descriptive qualitative. As for the data collection technique is done by observation, interviews and documentation. As for the research subjects include the head of government, as well as field staff and Disporapar Malang. The purpose of this study is to find out how the development of tourism in Malang City during the pandemic by using a public private partnership model, besides that also to find out what factors are obstacles in its implementation. The results of this study indicate that tourism development using the PPP cooperation model in Malang City has been running which then produces an application called TIC. However, for now the TIC application that was formed is still not linked or integrated with the Gojek application. Keywords: Public Private Partnership, Tourist Development, TIC (Tourist Information Center)